FEATURES THE DEVELOPMENT OF MILITARY TOURISM IN UKRAINE - Batychenko, S.; Melnik, L.; Savkov, P.; Storubliov , O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The article reveals the concept of military tourism. It is determined that military tourism is tourism on the battlefields and historical battles for all concerned, as well as for veterans and relatives of fallen soldiers, visits to existing and historical military facilities and training grounds, warships, submarines, military equipment, shooting from weapons on training grounds and shooting ranges, participation in military exercises and maneuvers, stay on training grounds as spectators – military tour, these also include tours to visit military concentration camps and prisons. Scientists have identified several classifications of subspecies of military tourism. Military tourism is military-historical, arms, military tourism, military tourism. There is also another classification of the division of military tourism into military-cognitive, military-adventure tourism, military-historical reconstructions of hostilities, illegal tours directly to the zone of military conflict. According to another approach, military tourism should be divided into three functional groups, taking into account the purpose and value orientations of tourists, as well as the emotional context of the trip: military-historical tourism, military tourism and military-event tourism. The resource base of military tourism in Ukraine is represented by objects of historical and cultural heritage of the princely era, the Cossacks, as well as the First, Second World and Civil Wars in the form of remnants of fortresses, defensive ramparts, graves, monuments and memorials to fallen soldiers and fellow villagers, places of executions or battles, military history museums, relevant exhibitions and festivals, military hotels. But not only visiting historical sites related to military events includes military tourism, but also tourists often want to try to shoot with weapons, ride tanks, armored personnel carriers, helicopters, as well as life in the military and participation in military training programs. In Ukraine, only one route has been developed and operates in the Transcarpathian region. It is established that military tourism in Ukraine is not fully mastered, but at the same time promising.